Outcome Evaluation of the Comprehensive Indian Resources for Community and Law Enforcement (CIRCLE) Project With Data From Nine Tribes in the United States, 1995-2004 - Brimley, Stephen ([Verlag nicht ermittelbar], 2008)
The data for this study were collected in Phase 2, the outcome evaluation, of the Comprehensive Indian Resources for Community and Law Enforcement (CIRCLE) Project. The CIRCLE Project was launched in the late 1990s to strengthen tribal justice systems and, through effective tribal-level planning and strategic comprehensive approaches, to better equip Native American nations to combat the interlinked community problems of crime, violence, substance abuse, and juvenile delinquency. The Native American nations invited to participate in the CIRCLE Project were the Northern Cheyenne, the Ogling Sioux, and the Zuni. Part 1, Participant Data, contains data on each of the Native American nations. The Northern Cheyenne data include variables on juvenile arrests between 1995 and 2003 for intoxication, curfew violations, disorderly conduct, and total arrests. The Oglala Sioux data include variables on police force stability and court pleadings. The Zuni data include variables on arrests for simple assault, public intoxication, driving while intoxicated (DWI), endangerment, domestic violence, and total arrests between 2001 and 2004. Part 2, United States Department of Justice Funding Data, contains data on funding given to the Northern Cheyenne, the Oglala Sioux, the Zuni, and six comparison Native American nations for fiscal years 1998 to 2003.